Application of Trichoderma asperellum Liquid Culture for Inducing Resistance of Chili Plant Against Fusarium Wilt - Albana, Hasan; Nurbailis, Nurbailis; Darnetty, Darnetty (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2026)
Fusarium wilt, caused by the fungus Fusarium oxysporum, is a significant disease that severely reduces the productivity of chili plants. This study investigated the potential of Trichoderma asperellum’s liquid culture as a biological control agent to control this disease and induce plant defense enzymes. Our findings demonstrated that applying the liquid culture of T. asperellum can significantly suppress disease development. Several treatments (A, D, E, and G) proved to be the most effective, showing the lowest disease severity and incidence. Furthermore, these treatments successfully increased the activity of key plant defense enzymes: peroxidase in roots (0.8746 U/g) and phenylalanine ammonia-lyase (PAL) in both roots (0.1886 μmol TCA/g) and stems (0.1653 μmol TCA/g). This increase in enzyme activity suggests that T. asperellum not only directly controls the pathogen but also triggers internal resistance mechanisms within the plant. While the liquid culture did not show a significant effect on plant growth, this may be due to the natural variability of T. asperellum and to additional factors, such as pests and environmental stress, in the field. Liquid culture of T. asperellum shows potential as a bioprotectant by suppressing the pathogen and enhancing host resistance.